The role of histone H3K36me3 in mammalian cell cycle regulation and genome stability - Armfield, LD (2019)
Although the molecular genetics regulating DNA replication onset have been studied in great detail, the epigenetic contribution to this step is poorly understood. H3K36me3 has been identified as a key factor regulating the catalytic ribonucleotide reductase subunit RRM2, suggesting an important role in DNA replication. To investigate this potential role, RNA-sequencing was carried out on SETD2 parental and CRISPR U2OS cell lines to identify genes differentially expressed in the absence of SETD2. Loss of SETD2 was found to lead to significantly reduced expression of a subset of E2F target genes critical for DNA replication and the G1/S transition. Consistent with this reduced expression, SETD2 deficient cells were found to have prolonged G1 delay, reduced replication fork progression and replication stress-associated 53BP1 bodies and γH2AX foci. Additionally, DNA under-replication was found to result in FANCD2-associated ultrafine anaphase bridges, micronuclei formation, and to G1 53BP1 bodies. A role was also identified for checkpoint-induced H3K36me3 in facilitating E2F transcription in response to replication stress. Together these findings support a dual role for H3K36me3 in the regulation of transcription of E2F target genes in the unperturbed G1/S transition, and as part of the replication stress response.